The scentscape: An integrative framework describing scents in servicescapes - Marc Girard; Anna Girard; Anna-Caroline Suppin; Silke Bartsch (jbm - Journal of Business Market Management, 2016)
The systematic use of ambient scents is a trend in service companies that is accompanied by increasing research attention. However, we lack a theoretical framework that ad-dresses ambient scents' specific role in physical surroundings of services. Thus, this article develops the 'scentscape', a model that describes the process of olfactory stimulation and its impacts on customers and employees in service environments. The paper extends Bitner's servicescape model (1992) and combines it with Gulas and Bloch's (1995) model of the influence of ambient scent, while integrating further results from a literature review in scent-related sciences. The paper consolidates existing theory into a holistic framework and discusses present inconsistent findings. The scentscape illustrates different scent sources, provides an overview of the process of scent perception and evoked internal and behavioral reactions in a servicescape. We derive 11 key findings, which need to be considered by managers and scientists when using / investigating scents in service environments. We identify key determinants and independencies to be considered by service academics and provide a wide range of future research directions. We provide crucial facts to guide practitioners in integrating ambient scents in service settings. The scentscape illustrates that the olfactory situation in an environment will influence individuals through their perceived air quality even if no ambient scents are introduced into the servicescape. Therefore, an active indoor air quality management should be generally a key task for managers, in order to avoid the potential negative impact of an unpleasant olfactory experience - and focus of further research.
urn:nbn:de:0114-jbm-v9i1.1547
Keywords: 650; Scent; Servicescape; Air quality; Integrative framework